Strategi Dinas Komunikasi dan Informatika dalam Mendukung Smart City Melalui Aplikasi Wargaku di Kota Surabaya - Rofpi, Ahmat; Tukiman (Journal of Governance Innovation, 2024)
Surabaya city is one of the cities in Indonesia that has implemented the concept of a smart city and has been awarded as the leading city in the main category of Smart City Rating. Based on the Duties and Functions of the Surabaya City Department of Communication and Informatics in 2021, the department introduced an application known as "Wargaku." The Wargaku Surabaya application serves as a platform for Surabaya citizens to submit complaints and obtain services. This research aims to describe the strategies of the Surabaya City Department of Communication and Informatics in supporting the smart city concept through the Wargaku complaint application in Surabaya. The research method used is qualitative descriptive, employing data collection techniques through observation, interviews, and documentation. The focus of this study is to utilize three strategic management indicators: Strategy Formulation, Strategy Implementation, and Strategy Evaluation. The research findings indicate that the strategies implemented to support the smart city concept through the "Wargaku" complaint application in Surabaya have been successful, as evidenced by the awards received at the PR Indonesia Awards (PRIA) in 2022 and the 4th Public Service Complaint Management Competition (P4) held by the Ministry of Administrative and Bureaucratic Reform (Kemenpan-RB), with support from the department's vision and mission, human resources, and infrastructure. Additionally, there has been an increase in the Community Satisfaction Index (IKM) every year. The evaluation conducted on the implementation of strategies is also considered good, as Standard Operating Procedures (SOP) have been formulated to handle various incoming complaints.